Factors Favouring Purchase Intention Of Hybrid Cars: An Empirical Study In Malaysia - Wong, Wei Yun (2014)
Global warming due to the impact of carbon dioxide has reached an alarming level. Primarily road transport is one of the main contributors to release carbon dioxide in the world. With the advancement of technology, variety of environmental friendly products exists in the market. One of them is the hybrid car; it is powered using combination of engine and battery. It is a promising product to control global warming. Thus, this project of work aims to identify the factors leading to hybrid car purchase intentions among Malaysian nationals. The factors that were examined in this study are environmental attitude, social influence, and awareness of responsibility while the moderating variable is the past experiences of non-hybrid car.